2016
DOI: 10.1063/1.4964677
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the Mo/Cu(In,Ga)Se2 interface in thin film solar cells: Formation and properties of the MoSe2 interfacial layer

Abstract: Being at the origin of an ohmic contact, the MoSe interfacial layer at the Mo/Cu(In,Ga)Se interface in CIGS (Cu(In,Ga)Se and related compounds) based solar cells has allowed for very high light-to-electricity conversion efficiencies up to 22.3%. This article gives new insights into the formation and the structural properties of this interfacial layer. Different selenization-steps of a Mo covered glass substrate prior to the CIGS deposition by co-evaporation led to MoSe interfacial layers with varying thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…For instance, in the preparation of CIGSSe solar cells, selenization of CIGS on Mo substrate is usually conducted at 450–540 °C for tens of minutes. This selenization process can lead to the generation of CIGSSe, together with selenization of Mo substrate surface to MoSe 2 , indicating the excellent permeation capability of selenium across the entire metal sulfide film at high temperature . Therefore, this method is difficult to generate gradient composition.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in the preparation of CIGSSe solar cells, selenization of CIGS on Mo substrate is usually conducted at 450–540 °C for tens of minutes. This selenization process can lead to the generation of CIGSSe, together with selenization of Mo substrate surface to MoSe 2 , indicating the excellent permeation capability of selenium across the entire metal sulfide film at high temperature . Therefore, this method is difficult to generate gradient composition.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, this barrier is lowered in the presence of Na [75]. The effect of MoSe 2 orientation on the Mo/MoSe 2 /absorber junction has been experimentally studied in the case of CIGSe technology [76,77]. It was found that while the back contact/ absorber contact resistance is twice as low for the MoSe 2 c-axis parallel orientation, the influence of Na plays a more important role on the contact resistance than the MoSe 2 orientation.…”
Section: Electrical Properties Of the Back Contactmentioning
confidence: 99%
“…Considering the experience accumulated for other chalcogenides such as CIGSSe, the adhesion onto glass/Mo substrates is expected to be good, if one can control the formation of Mo(S,Se) 2 and the synthesis parameters. In fact, the uncontrolled sulfurization/selenization of Mo can have a strong impact on the adhesion properties of the absorber on the substrate [100].…”
Section: Morphological Propertiesmentioning
confidence: 99%